Dual antiplatelet therapy after coronary artery bypass surgery: is there an increase in bleeding risk? A meta-analysis. (8th December 2017) - Zhao, Yejing; Peng, Hongyu; Li, Xiaonan; Qin, Yujun; Cao, Fangying; Peng, Ding; Liu, Jinghua
Abstract: OBJECTIVES: There is increasing evidence that dual antiplatelet therapy (DAPT) when compared with single antiplatelet therapy may improve venous graft patency after coronary artery bypass graft. However, it is not yet known whether postoperative administration of DAPT may increase the potential risk of bleeding, especially in the early postoperative period. METHODS: We searched studies on PubMed, Embase, Web of Science and the Cochrane Central Register of Controlled Trials. Relative risk (RR) was pooled with 95% confidence intervals (CIs) for dichotomous data. Prior subgroup analyses were performed to look for potential heterogeneity. RESULTS: Thirteen studies involving 23 591 participants were included. Our meta-analysis showed that DAPT does not increase the risk of major bleeding (randomized controlled trials group: RR = 1.28, 95% CI 0.95–1.71; cohort studies group: RR = 0.99, 95% CI 0.66–1.51) and minor bleeding (randomized controlled trials group: RR = 1.15, 95% CI 0.73–1.81; cohort studies group: RR = 0.84, 95% CI 0.37–1.93) when compared with single antiplatelet therapy. Meanwhile, DAPT does not increase the incidence of major bleeding events during hospitalization (randomized controlled trials group: RR = 1.27, 95% CI 0.91–1.78; cohort studies group: RR = 0.50, 95% CI 0.12–2.09). Sensitivity analyses showed that our results are stable, and there was no evidence of publication bias. CONCLUSIONS: DAPT does not increase the risk of major bleeding and minor bleeding when compared with single antiplatelet therapy. Postoperative administration of DAPT is considered to be safe in patients after coronary artery bypass graft, even in the early postoperative period.